Persistent Bacterial Coinfection of a COVID-19 Patient Caused by a Genetically Adapted Pseudomonas aeruginosa Chronic Colonizer - Qu, Jiuxin; Cai, Zhao; Liu, Yumei; Duan, Xiangke; Han, Shuhong; Liu, Jihong; Zhu, Yuao; Jiang, Zhaofang; Zhang, Yingdan; Zhuo, Chao; Liu, Yang; Liu, Yingxia; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Pseudomonas aeruginosa is a biofilm-forming opportunistic pathogen which causes chronic infections in immunocompromized patients and leads to high mortality rate. It is identified as a common coinfecting pathogen in COVID-19 patients causing exacerbation of illness. In our hospital, P. aeruginosa is one of the top coinfecting bacteria identified among COVID-19 patients. We collected a strong biofilm-forming P. aeruginosa strain displaying small colony variant morphology from a severe COVID-19 patient. Genomic and transcriptomic sequencing analyses were performed with phenotypic validation to investigate its adaptation in SARS-CoV-2 infected environment. Genomic characterization predicted specific genomic islands highly associated with virulence, transcriptional regulation and DNA restriction-modification systems. Epigenetic analysis revealed a specific N6-methyl adenine (m6A) methylating pattern including methylation of alginate, flagellar and quorum sensing associated genes. Differential gene expression analysis indicated that this isolate formed excessive biofilm by reducing flagellar formation (7.4 to 1624.1 folds) and overproducing extracellular matrix components including CdrA (4.4 folds), alginate (5.2 to 29.1 folds) and Pel (4.8-5.5 folds). In summary, we demonstrated that P. aeuginosa clinical isolates with novel epigenetic markers could form excessive biofilm, which might enhance its antibiotic resistance and in vivo colonization in COVID-19 patients.